Implementation of Retail Business Strategies and Their Relationship with Consumption Patterns in Department Stores in a COVID-19 Context - Obando Mantilla, Jerson Waldir (2023)
The objective of this study is to determine how retail business strategies are related to consumption patterns in department stores in a COVID-19 context. The methodology employed has a descriptive and correlational approach at a cross-sectional level. The data collection technique was a survey addressed to a sample of 384 consumers. The most significant result is the moderate and strong correlation coefficient of .702 for the variables with a p = .000 < .05. The results obtained show that retail business strategies are closely related to consumption patterns, which means that shopping habits can be created in customers.